Lean six sigma for small and medium sized enterprises a practical guide - Antony, Jiju; Vinodh, S.; Gijo, E. V. (Taylor & Francis, 2016)
A Practical Guide provides a roadmap for the successful implementation and deployment of LSS in SMEs. It includes five real-world case studies that demonstrate how LSS tools have been successfully integrated into LSS methodology